Effectiveness of Implantable Cardioverter Defibrillator Lead Coil Treatments in Facilitating Ease of Extraction - Hackler, Joseph W (2010)
BACKGROUND: Expanded polytetrafluoroethylene (ePTFE) coated and medical adhesive backfilled (MABF) implantable cardioverter defibrillator (ICD) coils have been promoted to reduce the fibrous ingrowth into coils that can complicate lead extraction. OBJECTIVE: The aim of this study was to test the hypothesis that ePTFE or MABF coatings are associated with greater ease of extraction. METHODS: Consecutive isolated ICD lead extraction cases were identified from a prospectively collected clinical database. Primary endpoints included total procedure and fluoroscopy times, radiation dose and fibrosis sites. Data were analyzed using univariate and multivariate analyses in total and propensity matched groups, adjusting for lead age and other factors. RESULTS: Among 329 patients (80% male; age 63.7±5.4 years), 284 (86.3%) had standard coil ICD and 45 (13.7%) had treated coil ICD leads extracted, of which 17 (5.2%) were ePTFE-coated and 28 (8.5%) were MABF ICD leads. ePTFE and MABF leads were associated with lower procedure and fluoroscopy times, radiation dose and fibrosis sites, including after adjustment for lead age, which was significantly shorter in the treated-coil leads. To further adjust for the difference in lead age, a propensity matched group was analyzed. Procedure time, fluoroscopy time, radiation dose, and brachiocephalic fibrosis remained significantly lower in the treated coil lead group. CONCLUSIONS: ePTFE and MABF treated coils appear to provide some incremental benefit in ease of extraction over conventional, non-treated coil ICD leads. Although many current ICD leads do not have fibrosis in-growth limiting strategies, our study may rationalize consideration of adding such technologies to future leads.